Sistem Pakar Mendiagnosa Penyakit Demam Berdarah Menggunakan Metode Certainty Factor - Resnawita; Hendrik, Billy (Journal of Information System and Education Development, 2023)
The increasingly rapid development of technology has changed the world, the launch of various new technologies has made people depend on technology for their work which is very helpful in solving various complex and simple problems. An expert system is a technology that has the abilities of certain experts who are very helpful in solving problems. An expert system is a system that is integrated with computer equipment in which there is knowledge, facts and reasoning techniques in solving problems that usually can only be solved by an expert in that field. Such as an expert system that analyzes dengue fever by relying on the symptoms felt by a person. as a decision maker. Dengue hemorrhagic fever (DHF) is a disease caused by dengue virus infection. DHF is an acute disease with clinical manifestations of bleeding which causes shock which leads to death. This system was designed with the aim of being a means of resolving problems surrounding dengue fever using the certainty factor method. Certainty Factor is a method for proving whether a fact is certain or uncertain in the form of a metric which is usually used in expert systems. The percentage of confidence obtained by the expert system for diagnosing dengue fever reached 94% by referring to the data provided by the user to the expert system.